Dental caries experience in 12-year-old schoolchildren from Araruna, Paraíba, Brazil (Revista Contexto & Saúde, 2026)
Objective: To identify the dental caries experience among 12-year-old schoolchildren from Araruna, Paraíba, Brazil, and its associated risk factors, including diet, oral hygiene, and socioeconomic conditions.Methods: This was a cross-sectional observational epidemiological study conducted with a sample of 151 12-year-old schoolchildren enrolled in public and private schools in Araruna, Paraíba, Brazil. Socioeconomic data were obtained from school enrollment records, and structured questionnaires with closed-ended questions were administered to assess oral hygiene habits and dietary patterns. Clinical oral examinations were also performed. Data collection took place between July and October 2022. Statistical analyses were conducted using Microsoft Excel® and IBM SPSS Statistics® version 20.0.Results: The sample comprised male (62; 41.1%) and female (89; 58.9%) schoolchildren, with a predominance of mixed-race individuals (93; 61.6%) and residents from urban areas (89; 58.9%). The mean CPO-D index (Decayed, Missing, and Filled Teeth) was 4.43. Among the variables analyzed, significant associations with dental caries experience were observed in children from families earning up to half the minimum wage (102; 93.1%), those who visited the dentist between 6 months and 1 year (96; 63.5%), those receiving government social assistance (93; 92.1%), and those consuming potentially cariogenic foods, including biscuits (106; 85.4%), breakfast cereals (18; 100%), yogurt/dairy beverages (88; 89.8%), and sweet popcorn/peanuts (111; 89.5%).Conclusion: Dental caries experience in Araruna, Paraíba, Brazil, showed a high mean CPO-D index, with the decayed component being the most prevalent. The presence of dental caries, defined as CPO-D ≥ 1, was mainly influenced by socioeconomic factors and dietary patterns.
Keywords: Dental caries; Oral hygiene; Socioeconomic factors; Diet